Pengaruh Waktu Ekstraksi dengan Metode Microwave Assisted Extraction (MAE) terhadap Aktivitas Antioksidan Ekstrak Daun Belimbing Wuluh (Averrhoa Bilimbi L.) - Swara, I Made Arya Bhaskara; Puspawati, Gusti Ayu Kadek Diah; Widarta, I Wayan Rai (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 4 (2023): Jurnal ITEPA, 2023)
Wuluh starfruit leaves have a very high antioxidant content. Antioxidants are substances that can reduce speed, postpone, or stop lipids from oxidizing or other easily oxidized components from oxidizing. The precise extraction time can have an impact on antioxidant activity. The purpose of this study was to investigate the effect of extraction time in the Microwave Assisted Extraction (MAE) technique on the antioxidant activity of wuluh starfruit leaf extract, as well as the precise extraction time in the MAE technique for producing the highest antioxidant activity starfruit leaf extract. The study employed a fully randomized design (CRD) with extraction time treatment levels of 3,5,7,9,11, and 13 minutes. There were 18 experimental units with three repetitions of each treatment. The Duncan Multiple Range Test (DMRT) was used to determine if the therapy had any impact on the parameters after the data were subjected to analysis of variance. The findings demonstrated that the yield, total phenol contents, total flavonoids contents, total tannin contents, total vitamin C contents, and IC50 were significantly influenced by the extraction duration. The best extraction time for wuluh starfruit leaves extract used the MAE method was 5 minutes with a yield of 26.75%, total phenol 621.60 mg GAE/g, total flavonoids 321.52 mg QE/g, total tannins 298.83 mg TAE/g, total vitamin C 595.44 mg AAE/g and IC50 28.35 ppm.